Green synthesis of AgeZnO nanoparticles: Structural analysis, hydrogen generation, formylation and biodiesel applications - Yadav, L.S. Reddy (Elsevier, 2019)
The present work reveals the green combustion preparation of the Ag-doped ZnO nanoparticles (NPs) using turmeric root extract as a fuel. The structure and morphology of Ag-doped ZnO NPs were investigated by several analytical techniques such as XRD (X-Ray Diffraction), SEM (Scanning Electron Microscopy), TEM (Transmission Electron Microscopy), FTIR (Fourier Transform Infrared), Raman, XPS (XRay Photoelectron Spectroscopy), and UV-Visible Spectroscopy (UVeVis). From XRD, the crystallite size was found to be about 45 nm which agrees with the TEM results. SEM micrographs reveal the spherical shaped agglomerated particles. XPS measurement anticipates that Ag is mainly in the metallic state and ZnO is in the Wurtzite structure. UVeVisible spectroscopy shows the absorbance peak at 368 nm. Biodiesel synthesis from Terminalia belerica oil with AgeZnO as a nanocatalyst has been studied. AgeZnO nanoparticles show hydrogen evolution up to 214 mmolg 1h 1. A convenient synthesis of Na-protected formamides from protected amino acids was described using AgeZnO as a catalyst. This method provides good yield of formamides with excellent purity after removal of the catalyst